Perfil imunofenotípico de linfócitos em crianças nascidas de mães com asma e renite alérgica, em Belo Horizonte - Solange Aparecida Pacheco (2003)
BACKGROUND: Several reports have established that allergic diseases are increasing worldwide. Despite our knowledge that heredity influences the progress of asthma in childhood, it is been claimed that fetal environmental factors occurring during pregnancy might be of importance for the development of the disease. Attempts to identify a predictive marker of disease development in the cord blood cellularity have given conflicting results. Both proliferative and cytokine responses have been detected in cord blood mononuclear cells (CBMC), suggesting in utero allergen priming. OBJECTIVE: To determine if lymphocyte profile and activation status are altered by maternal history of allergy and to investigate the relationship between lymphocyte activation status and the development of allergic disease at twelve month of age, in a longitudinal study of high-risk children. METHODS: Prevalence of allergy and allergen sensitization were determined in pregnant women, attending pre-natal service in Belo Horizonte, Brazil (n=210). They were classified, based on clinical history and skin test, in Case and Control groups. Determination of the CD45 isoform of T cell subsets, as well as the determination of T cells expressing IL-2 receptor (CD25) and HLA~DR were evaluated in CBMC and peripheral blood mononuclear cell (PBMC) obtained from pregnant women (group Case, n = 16; group Control, n = 14). Prospective newborns clinical follow-up was performed for 1 year. RESULTS: The prevalence of allergic disease during pregnancy was 16,6% for asthma and 29% for rhinitis, and house mites were the most frequent allergen (in Case group, Dermatophagoides pteronissinus, 95%; D. farinae, 70%). The frequency of CD4+ T cells carrying CD45RO marker was higher in PBMC of allergic pregnant women (48,4% i 16,1 versus 23,5% 1 22,1), but no difference in CBMC activation status profile (CD19+CD5+, CD3+CD25+, CD3+l-lLA-DR+, CD4+CD45RA+,- CD4+CD45RO+, CD8+CD45RA+, CD8+CD45RO+) between both groups was observed. At 12 months of age, 25% Case group children but none of the Control group had developed an atopic disease. CONCLUSION: In our population, CBMC activation profile did not differ between the two groups, so its determination could not predict the development of atopic diseases, for the first year of life.